A review of current status of cell-based therapies for aortic aneurysms - Aika Yamawaki-Ogata; Masato Mutsuga; Yuji Narita (BMC, 2023)
Abstract An aortic aneurysm (AA) is defined as focal aortic dilation that occurs mainly with older age and with chronic inflammation associated with atherosclerosis. The aneurysmal wall is a complex inflammatory environment characterized by endothelial dysfunction, macrophage activation, vascular smooth muscle cell (VSMC) apoptosis, and the production of proinflammatory molecules and matrix metalloproteases (MMPs) secreted by infiltrated inflammatory cells such as macrophages, T and B cells, dendritic cells, neutrophils, mast cells, and natural killer cells. To date, a considerable number of studies have been conducted on stem cell research, and growing evidence indicates that inflammation and tissue repair can be controlled through the functions of stem/progenitor cells. This review summarizes current cell-based therapies for AA, involving mesenchymal stem cells, VSMCs, multilineage-differentiating stress-enduring cells, and anti-inflammatory M2 macrophages. These cells produce beneficial outcomes in AA treatment by modulating the inflammatory environment, including decreasing the activity of proinflammatory molecules and MMPs, increasing anti-inflammatory molecules, modulating VSMC phenotypes, and preserving elastin. This article also describes detailed studies on pathophysiological mechanisms and the current progress of clinical trials.